Universal antiretroviral therapy (ART) for infants and young children living with HIV: assessing the effect of guideline changes on ART initiation characteristics and treatment outcomes in resource-limited settings - Iyun, Victoria Oluwatoyin (Department of Public Health and Family Medicine, 2022)
Background Sub-Saharan Africa is home to >90% of all children living with HIV worldwide. Since 2008, there has been a shift in paediatric HIV treatment towards universal antiretroviral therapy (ART) allowing for immediate initiation of ART, regardless of clinical or immunologic status initially for infants, and subsequently for progressively older, and ultimately all children. Given the scale-up of early infant diagnosis (EID) and early initiation of ART for infants and young children who are especially vulnerable to rapid progression of HIV and mortality, access to paediatric antiretroviral therapy (ART) services has substantially improved across sub-Saharan Africa (SSA). However, with the changing guidelines and practices, the demographic and clinical characteristics of infants and young children infected in recent years may vary from those infected before the widespread uptake of prevention of mother-to-child transmission of HIV (PMTCT) services and universal ART. This study therefore sought to understand the impact of changing guidelines on key metrics of the paediatric HIV care continuum, including timeliness of ART initiation, mortality, program retention and viral load suppression in order to examine effectiveness of ART in infants and young children enrolled in routine ART programs. Methods Using data from the International epidemiologic Databases to Evaluate AIDS Collaboration (IeDEA), this thesis described the temporal trends in the ART initiation characteristics in a total of 1692 infants initiating ART < 1 year of age and 32,220 young children initiating ART < 5 years of age between 2006-2017 in South Africa and SSA respectively. The trends in outcomes including mortality, loss to follow-up (LTFU), viral suppression. Associated determinants were also examined. Findings The result chapters of this thesis are presented in the form of journal papers in different stages of publication. The first paper reports that disease severity characteristics among all children starting ART aged <5 years in sub-Saharan Africa improved over time. Mortality declined substantially, however, LTFU remained unchanged with one in five children continuing to be lost before two years on ART. There was substantial heterogeneity in outcomes across country income groups. The second paper presents data on infants with HIV starting ART ≤3 months of age in South Africa. Findings suggests a that growing proportion of infants started ART at younger ages and with less advanced HIV disease. Mortality was 10.6% (7.8%-14.4%) in 2006- 2009 and decreases progressively to 4.6% (3.1%-6.7%) in 2013-2017 (p< 0.001), with LTFU remaining unchanged across calendar periods (p=0.274). The third paper presents findings on the trends in viral suppression (viral load [VL] < 400 copies/ml) and immunologic response up to 12 months on ART in infants who started treatment at < 3 months of age. By 6 and 12 months on ART, 56% and 65% infants achieved virologic suppression and the median (IQR) CD4 percentages increased slightly to 30% (22-37) and 31% (25-39) respectively, from a median of 27% (18-38) at ART initiation. There was a trend towards poorer viral suppression levels among infants initiating early ART in recent calendar years, despite improvement in CD4% and lower VL at ART initiation. The final paper suggests that good long-term viral suppression (<70%) among infants in routine care is achievable. However, infants staring ART between 0- 3 months vs those starting at 4-12 months of age had the lowest rate of viral suppression at all timepoints during a follow-up period of five years on ART. Conclusions Findings from this thesis suggest an increase in earlier ART initiation for infants and young children, with associated improvement in health status at ART initiation and declines in mortality following universal ART recommendations. However, substantial inequities existed across country income groups and a quarter of children on antiretroviral therapy across SSA continue to experience LTFU. In addition findings highlight suboptimal short and long-term viral suppression in infants acquiring HIV in the era of birth diagnosis and early infant ART. Targeted interventions are therefore urgently required to improve the outcomes of infants and young children living with HIV, especially among infants initiating ART before three months of age and children in low and lower-middle-income countries.